1994
DOI: 10.1007/bf01476425
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of microvascular decompression for trigeminal neuralgia with reference to probability of recurrence

Abstract: Sixty-one patients with trigeminal neuralgia who underwent microvascular decompression were analysed. Vascular compression of the trigeminal nerve root was found in all cases. The recurrence rate of pain in this series was 18% with an average follow-up of 80 months (range: 13 to 126 months). Ten patients developed recurrence of their trigeminal neuralgia during follow-up. Fifteen factors, including the clinical and operative findings in the pain-free patients versus the 10 patients with recurrence were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 20 publications
8
45
0
1
Order By: Relevance
“…This last point was criticized by Klun [26] in whose experience no data matching symptoms duration with the postoperative success were evident. More general agreement is evident concerning the analysis of correlation between an unclear neurovascular conflict and pain persistence or recurrence [10,26,27]. In our study no outcome differences were observed between cases harboring a clear or an unclear neurovascular conflict.…”
Section: Discussionsupporting
confidence: 79%
“…This last point was criticized by Klun [26] in whose experience no data matching symptoms duration with the postoperative success were evident. More general agreement is evident concerning the analysis of correlation between an unclear neurovascular conflict and pain persistence or recurrence [10,26,27]. In our study no outcome differences were observed between cases harboring a clear or an unclear neurovascular conflict.…”
Section: Discussionsupporting
confidence: 79%
“…Of the 61 patients, 10 (16%) had recurrence within 2 years of surgery. 38 Tronnier et al reviewed 225 cases in which patients were treated with MVD and found that 63% of the patients had 20 years of pain relief. 41 Sindou et al evaluated 120 patients after MVD, with a mean followup period of 41 months; 83.3% and 79% of patients had pain relief from sitting craniotomy and lateral approach, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature reveals a wide range of recurrence rates of approximately 6%-41%. 5,6,8,10,11,22,23,25,[27][28][29]33,[36][37][38][39][41][42][43][44] Surgical alternatives after recurrence include repeat exploration for recurrent vascular compression and microvascular decompression (MVD), internal neurolysis, or radiofrequency lesioning. Other alternatives for recurrent TN include partial or complete sensory rhizotomy, balloon rhizotomy, glycerol injections, and radiosurgery.…”
mentioning
confidence: 99%
“…Recurrence can be ascribed to the postoperative fibrotic adhesions formed around the nerve [56], to the intrinsic lesion [67] and especially to the absence of NVC.…”
Section: Is Mvd the Definitive Treatment For Tn?mentioning
confidence: 99%